KLASIFIKASI MUTU 11 JENIS ROTAN INDONESIA BERDASARKAN KERAPATAN DAN KETEGUHAN LENTUR - Rohmah Pari; Abdurachman; Jasni; Titi Kalima (Jurnal Penelitian Hasil Hutan, 2018)
Rattan is a lignocellulose plant that can be used for furmiture and other handicraft product. Quality and characteristics of the rattan species should be identified to comply with their utilization purposes. This research aimed to study the quality classification of 11 less used rattan species from Kalimantan, Sulawesi and Sumatera based on their physical properties (density) and mechanical properties (bending strength). The testing method applied was modified from ASTM D143-94. This modification was carried out because the formula used in ASTM is for square cross-section while rattan has cylindrical cross-section. The study of 11 species of rattan, based on the physical and mechanical properties, showed that three species of rattan from Kalimantan were classified in to class II – I (Calamus lobbianus), class III (Daemonorops fissa) and class IV – III (C. marginatus), while the three species of rattan from Sulawesi were grouped in to class I (C. robinsonianus), class II (C. scleracanthus) and class II – III (C. mindorensis). The remaining five species of rattan from Sumatera were categorized in class I – II (C. rugosus), class II – I (C. spectatissimus), class I – III (D. longipes), class II – III (D. verticillaris), and class III (D. sepal). These results could be used as a consideration for utilization of high quality rattan for furniture material that hold heavy load while low quality rattan may be used for holding light load only.